Evolution and determinants of rent burdens in Germany - Teresa Backhaus; Kathrin Gebers; Carsten Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The affordability of housing has become a major topic of discussion in Germany among both social scientists and the public at large. Using data from the German Socio-Economic Panel (SOEP), we provide rent-income ratios over more than two decades and show how they change with households' disposable needs-adjusted income. We find a substantial increase in the ratios over the 1990s. In the decade that followed, they remained relatively constant. Moreover we find that rent-income ratios decrease in income at a decreasing rate, suggesting that rising square-meter prices put particular financial pressure on low-income households. Our analysis also indicates economies of scale from shared living space for multi-member households.
Keywords: D1; D3; D6; I3; O18; 330; home; amenities; and contributions of private households; income; taxes; and social security